FORMATION OF ORGANIZATIONAL CULTURE OF THE BORDER GUARD OFFICER: RESULTS OF PEDAGOGICAL EXPERIMENT - Boreichuk, D.H (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article highlights the results of a pedagogical experiment on the formation of organizational culture to future border guard officers in the process of their professional training. The organizational culture of future border officers is treated as a professionally important property, which includes knowledge about the mission and values of the border agency, the ability to maintain and promote the cohesion of the border team and manifests itself in the observance of professional standards in interpersonal interaction and in the performance of tasks of border protection, self-organization and self-discipline. The organizational culture of the border guard officer as a leader is evidenced by a set of achievements of the border unit, the effectiveness of innovations, reasonable organization of work, psychological climate, external and internal communications. The peculiarities of pedagogical experiment on formation of organizational culture to future border guard officers in the process of their professional training are highlighted; the main pedagogical conditions of the formation of organizational culture are described. For strengthening the value-motivating attitude of cadets to the study of topical problems of organizational culture of the border guard officer, a special course «The organizational culture of border guard officers» is offered. The course is necessary to provide cadets with theoretical and practical knowledge about the organizational culture of the border guard officer, its basic requirements, the theory and practice of forming a system of organizational culture, the use of principles, types, leadership tools and creating a strong team. During the experimental work the importance is given to the development of the future border officers' skills of teamwork by means of social and psychological training, development of skills of constructive interpersonal interaction in a team, effective ways of solving problems in a team, various options for conflict resolution, the use of individual models of situational analysis of interpersonal problems. The importance of using modern dialogue forms, methods, interactive learning technologies, modelling of life situations, the use of role-playing games, joint problem-solving for the development of cadets' skills in professional communicative interaction is revealed. Considerable attention is paid to the development of organizational skills and managerial decision-making and leadership skills to future border guard officers by gradually introducing into the educational process situational tasks of professional direction with complication of their content in each course of training.